Commemorating Peterloo : violence, resilience and claim-making during the Romantic era - Demson, Michael; Hewitt, Regina, 1959- (Edinburgh critical studies in romanticism., 2019)
Two hundred years after the massacre of protestors in Manchester, known as Peterloo, distinguished scholars of Romantic-era literature join together in this commemorative volume to assess the implications of the violence.